050 A novel role for b-type natriuretic peptide (BNP) as a safe and effective rule-out test in patients referred to rapid access chest pain clinics; results of a large, prospective 1-year follow-up study. (22nd September 2015) - George, J; Mackle, G; Struthers, A D
Abstract : Background: Rapid access chest pain clinics (RACPCs) are commonplace but studies have shown that at least half of RACPC referrals have a final diagnosis of non-cardiac chest pain. A safe and effective pre-screening test before RACPC referral might reduce referrals by general practitioners, reduce costs and relieve unnecessary patient anxiety. The ability of BNP to help diagnose CAD has been confirmed in several recent studies. Its ability as a rule-out test in patients presenting with all-cause chest pain is not known. Aims/Objectives: We aimed to determine if a near-patient pre-screening BNP would be a simple but effective rule-out test to safely exclude a cardiac cause for chest pain and reduce unnecessary referrals to RACPCs. An additional objective was to determine whether a particular BNP level at presentation is able to identify those RACPC patients who suffer cardiac events in the following 12 months. Other studies in different populations suggest BNP is very accurate at predicting future events. Methods: Six hundred and twenty-five patients attending Rapid Access Chest Pain clinics in Tayside were recruited into the study over a 2-year-period. Each patient had demographic data, a near patient BNP level (Biosite TM ), clinical and laboratory measurements documented. The initial diagnosis was considered positive for IHD if the patient had a positive troponin T, was referred for angiography or coronary artery bypass grafting. All patients were then followed up 1-year after their initial RACPC attendance using hospital medical records, primary care records and telephone calls to document further RACPC attendance, hospitalisations for chest pain and survival data. Results and Discussion: The average age of the patients was 60.0 years and 45% were female. The Negative predictive value (NPV) and Sensitivity of a BNP level ≤10 pg/ml for ruling out cardiac chest pain was 97.9% and 94% respectively. For the 1-year follow-up study, when corrected for age, sex and established risk factors such as hypertension, hypercholestrolaemia, diabetes, smoking and BMI, a BNP cut-off of greater than 10 pg/ml significantly predicted further hospitalisations for chest pain in the following 12-months compared to patients who presented with a BNP of less than 10 pg/mL (p<0.001). Of 141 (23%) patients with a BNP of less than 10 pg/ml, 3 (0.02%) were re-admitted for chest pain in the following year and of those none (0%) had a positive troponin T on re-admission. Conclusion: A near patient BNP level ≤10 pg/ml is a safe and effective rule-out test for possible ischaemic heart disease in patients presenting with chest pain. Patients with BNP levels <10 pg/ml are significantly less likely to be admitted with cardiac chest pain in the following 12 months. In this study, a cut-off value of 10 pg/ml would safely reduce RACPC referrals by 23%.